2018
DOI: 10.3847/1538-4357/aae92c
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of ICMEs with Low Mean Carbon Charge State Plasmas Detected from 1998 to 2011

Abstract: We present a statistical study of 219 ICMEs measured by both ACE and WIND from 1998 to 2011. ICME plasmas are defined as possessing cold materials if the carbon average charge states are lower than those of the preceding solar wind by three standard deviations and the carbon ionic temperature is lower than 106.05 K. A total of 69 ICMEs were identified as containing cold materials. These ICMEs tend to have speeds in the range of 300–600 km s−1, with durations between 2 and 6 hr. Cold materials tend to be presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The work reported that magnetic clouds exhibit higher ionic charge states than non-magnetic clouds. In addition, statistical results demonstrated that fast magnetic clouds have higher charge states and relative elemental abundances (except the C/O) than slow ones (Owens, 2018;Huang et al, 2020), and cold prominence plasmas with lower charge states can be detected within ICMEs near 1 au (Lepri and Zurbuchen, 2010;Gilbert et al, 2012;Sharma and Srivastava, 2012;Wang, Feng, and Zhao, 2018;Feng et al, 2018). Zurbuchen et al (2016) performed a comprehensive analysis of the elemental abundances of 310 ICMEs on Richardson and Cane's catalog from 1998 March to 2011 August (Richardson and Cane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The work reported that magnetic clouds exhibit higher ionic charge states than non-magnetic clouds. In addition, statistical results demonstrated that fast magnetic clouds have higher charge states and relative elemental abundances (except the C/O) than slow ones (Owens, 2018;Huang et al, 2020), and cold prominence plasmas with lower charge states can be detected within ICMEs near 1 au (Lepri and Zurbuchen, 2010;Gilbert et al, 2012;Sharma and Srivastava, 2012;Wang, Feng, and Zhao, 2018;Feng et al, 2018). Zurbuchen et al (2016) performed a comprehensive analysis of the elemental abundances of 310 ICMEs on Richardson and Cane's catalog from 1998 March to 2011 August (Richardson and Cane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from heavy ions, plasma moments, and the interplanetary magnetic field (IMF) were reported. The lower charge states of C, O, and Fe ions indicate the lower freeze-in ionic temperature (Lepri & Zurbuchen 2010;Song et al 2016;Kocher et al 2017;Feng et al 2018;Wang et al 2018;Rivera et al 2019). The proton density, proton temperature, and singly ionized helium support the existence of cold and dense chromospheric materials (Schwenn et al 1980;Burlaga et al 1998;Gopalswamy et al 1998;Yao et al 2010).…”
Section: Introductionmentioning
confidence: 94%
“…In this work, we select ICMEs from a list reported by Cane & Richardson (2003) and Richardson & Cane (2010). 3 The segments of PCs in ICMEs are selected from a list of carbon cold materials in Feng et al (2018). It should be noted that these carbon cold materials in ICMEs are selected by carbon mean charge and carbon ionic temperature compared to 24 hr long QSW preceding the ICME (Feng et al 2018).…”
Section: Data and Training Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the signatures of heavy ions in ICMEs is that the average charge states are usually higher than those in the solar wind, which indicates a stronger heating process in the initiation of CMEs (Wimmer-Schweingruber et al 2006;Gruesbeck et al 2011;Henke et al 2001). Meanwhile, unusually low charge states of heavy ions in ICMEs have also been reported (Lepri & Zurbuchen 2010;Song et al 2017;Feng et al 2018), which are thought to be possibly related to the cold prominence plasma. When a CME erupts and propagates outward, the electron density decreases rapidly with solar distance.…”
Section: Introductionmentioning
confidence: 99%